Advanced interatrial block is an electrocardiographic marker for recurrence of atrial fibrillation after electrical cardioversion. (1st December 2018) - Fujimoto, Yuhi; Yodogawa, Kenji; Maru, Yu-jin; Oka, Eiichiro; Hayashi, Hiroshi; Yamamoto, Teppei; Iwasaki, Yu-ki; Hayashi, Meiso; Shimizu, Wataru
Abstract: Background: Early recurrence of atrial fibrillation (AF) is common following a successful electrical cardioversion (ECV). The purpose of this study was to investigate the hypothesis that AF recurrence is related to atrial electrical inhomogeneity, which may influence the P wave characteristics. Methods: Two hundred ninety-one consecutive persistent AF patients who underwent ECV were enrolled, and evaluated for AF recurrences one month after the ECV. Patients with open-heart surgery, a history of catheter ablation, and an unsuccessful ECV were excluded. The P wave duration, dispersion and P wave morphology were evaluated by 12‑lead ECGs 30 min after the ECV. Results: In total, 141 patients were investigated. One month after the ECV, 60 (43%) patients maintained sinus rhythm. The advanced interatrial block (aIAB; P wave duration >120 ms and biphasic P waves in the inferior leads) (Hazard ratio [HR], 4.51; 95% confidence interval [CI] 1.45–14.01, P = 0.009), P wave dispersion (HR, 1.06; 95%CI 1.02–1.09, P = 0.001), and duration of AF per month (HR, 1.03; 95%CI 1.01–1.04, P = 0.004) were independent predictors of AF recurrence. An aIAB was not associated with structural parameters such as the left atrial volume index or right atrial area. There were no differences in the serum BNP level and frequency of administering anti-arrhythmic drugs between the patients with and without recurrence. Conclusions: The risk of AF recurrence after the ECV can be predicted by the P wave characteristics. A longer P wave dispersion and the duration of AF also had a tendency for recurrence. Highlights: Prediction of AF recurrence after cardioversion is important for the clinical therapeutic strategy. The advanced interatrial block was the strong predictor of AF recurrence. Patients with a longer P wave dispersion and the duration of AF had a tendency for recurrence.